EVALUASI KINJERJA PETUGAS UNIT AIRPORT RESQUE AND FIRE FIGHTING (ARFF) DALAM MELAKUKAN PERAWATAN KENDARAAN UTAMA DI BANDAR UDARA INTERNASIONAL ADI SOEMARMO BOYOLALI - Rico F.G Langodai; Suprapti (Universitas Sains dan Teknologi Komputer, 2023)
The Airport Resque and Fire Fighting (ARFF) Unit is a unit tasked with providing safety services when an accident occurs in the airport area. Providing safety services certainly requires supporting facilities, one of which is the main vehicle or fire engine, which is the main facility for carrying out rescues when an accident occurs in the airport area. The aim of this research is to determine the performance of ARFF unit officers in carrying out maintenance on the main vehicle and to find out whether the main vehicle and supporting equipment available on the main vehicle meet the established standards. This study uses a qualitative method. The data collection techniques used were observation, interviews and documentation carried out at PT Angkasa Pura I Adi Soemarmo Boyolali International Airport with placement in the Airport Resque and Fire Fighting (ARFF) unit. The results of research regarding the main vehicles available at the Airport Resque and Fire Fighting (ARFF) unit are the lack of funds available to carry out maintenance such as replacing supporting equipment or spare parts, fuel and oil changes. The impact of the lack of funds to carry out maintenance is that the performance of ARFF unit officers is less than optimal in carrying out main vehicle maintenance.